Ontologia para teste de desempenho de software - Freitas, Artur Luiz Silva da Cunha (2013)
Software testing is a technique used to provide information about the quality of a software operating in a specific context. The test responsible for assessing the performance and efficiency of a software in a usage scenario is known as performance testing. The development of a performance test is a task that requires testers with expertise related to the tools, activities and metrics of the domain. To represent this knowledge, this work proposes an ontology on the domain of performance testing. Ontology is a knowledge representation technique considered state of the art within the Artificial Intelligence. Moreover, one contribution of this research is to identify, based on the analysis of related works, what is known about the use of ontologies in software testing. Finally, the proposed ontology is evaluated by domain experts, compared with related ontologies and explored in applications designed to help testers regarding the planning and elaboration of performance tests.